Contextualizing Justice and Human Dignity in Rwanda: The (Global Journal of Human-Social Science, 2016)
The word "Inyenzi", which is a Kinyawanda word for cockroaches, came into political lexicon in Rwanda following the Revolution of 1959 in that East Central African nation. Following that Revolution, a hitherto politically dominant ethnic fraction of a broadly homogeneous population -the Tutsi, lost its status to an erstwhile dominated group -the Hutu. Consequent upon this scenario, and in order to escape state-sponsored persecution, the Tutsi fanned out in different directions into the countries of the Great Lakes region -Burundi, Uganda, Tanzania, DR. Congo. From these countries of asylum, Tutsi refugees began to carry out sporadic raids into Rwanda, in an effort to get even with the authorities, but more ostensibly to forcibly re-enter Rwanda and re-assume its former dominant position. The now dominant Hutu ethnicity responded by referring to them as cockroaches, so as to encourage not just disdain and hatred for them from the larger society, but a murderous pre-disposition, much like the natural human disposition toward cockroaches. It is the extent to which this contextualizes the denial of justice and human dignity that this paper seeks to determine. The paper also evaluates the consequences of this exercise for peace and development in the Great Lakes region of Africa.
Keywords: justice; human dignity; Hutu; Tutsi; peace; development